The Effect Of Information System Quality And Information Quality On User Statisfaction Accounting Information System - Jufli Anita Ranti M (TRIGIN PUBLISHER, 2021)
The purpose of this study was to examine the influence of the quality of information and quality of information systems to the satisfaction of the end users of accounting information systems. This research model is used with reference to the model in using information technology system that is the Technology Acceptance Model (TAM) developed by DeLone and McLean. Data were collected from questionnaires given to 110 employees at Kodam I/BB as information systems user. Questionnaires were received back from 78 questionnaire respondents, and only 74 questionnaires that can be used for further analysis. Data analysis was performed using regression analysis through SPSS version 17. The results showed that the quality of information systems and information quality affects the end-user satisfaction of information system. The results showed that the quality of information system and the quality of information has a positive and significant influence on the accounting information system of user satisfaction in Kodam I/Bukit Barisan. This shows that the better the quality of information system and the quality of information applied to the level of satisfaction of users of accounting information system are getting higher.